2023
DOI: 10.3390/cells12030439
|View full text |Cite
|
Sign up to set email alerts
|

People with Primary Progressive Multiple Sclerosis Have a Lower Number of Central Memory T Cells and HLA-DR+ Tregs

Abstract: The importance of circulating immune cells to primary progressive multiple sclerosis (PPMS) pathophysiology is still controversial because most immunotherapies were shown to be ineffective in treating people with PPMS (pwPPMS). Yet, although controversial, data exist describing peripheral immune system alterations in pwPPMS. This study aims to investigate which alterations might be present in pwPPMS free of disease-modifying drugs (DMD) in comparison to age- and sex-matched healthy controls. A multicentric cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…While the neuropathological features in the brain of patients with relapsing or progressive MS are essentially similar, the relative incidence of different lesion characteristics change with time of disease evolution. 33 OCR is an effective treatment for both RR-and PP-MS, and CD20 + B cells are thought to act as cytokine and antibody producers or as antigen-presenting cells essential for T-cell activation in both relapsing and progressive MS. 33 As for progressive disease, longer disease duration and a higher degree of disability were shown to correlate only with NK cell subsets alterations in patients with PP-MS. 33 Concerning T cells, results were inconsistent, as patients with progressive disease might have lower numbers of effector memory CD4 + T cells or a lower percentage of both naive and effector memory CD8 + T cells compared to healthy controls. 33 However, it was suggested that memory T-cell subsets might differ among relapsing and progressive MS. 33 Furthermore, TH17 subsets were shown to be increased in both PP-and SP-MS patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the neuropathological features in the brain of patients with relapsing or progressive MS are essentially similar, the relative incidence of different lesion characteristics change with time of disease evolution. 33 OCR is an effective treatment for both RR-and PP-MS, and CD20 + B cells are thought to act as cytokine and antibody producers or as antigen-presenting cells essential for T-cell activation in both relapsing and progressive MS. 33 As for progressive disease, longer disease duration and a higher degree of disability were shown to correlate only with NK cell subsets alterations in patients with PP-MS. 33 Concerning T cells, results were inconsistent, as patients with progressive disease might have lower numbers of effector memory CD4 + T cells or a lower percentage of both naive and effector memory CD8 + T cells compared to healthy controls. 33 However, it was suggested that memory T-cell subsets might differ among relapsing and progressive MS. 33 Furthermore, TH17 subsets were shown to be increased in both PP-and SP-MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…33 OCR is an effective treatment for both RR-and PP-MS, and CD20 + B cells are thought to act as cytokine and antibody producers or as antigen-presenting cells essential for T-cell activation in both relapsing and progressive MS. 33 As for progressive disease, longer disease duration and a higher degree of disability were shown to correlate only with NK cell subsets alterations in patients with PP-MS. 33 Concerning T cells, results were inconsistent, as patients with progressive disease might have lower numbers of effector memory CD4 + T cells or a lower percentage of both naive and effector memory CD8 + T cells compared to healthy controls. 33 However, it was suggested that memory T-cell subsets might differ among relapsing and progressive MS. 33 Furthermore, TH17 subsets were shown to be increased in both PP-and SP-MS patients. 34 Another important factor that needs to be considered is age, even more so as the number of elderly MS patients will continue to grow due to an increased life expectancy among the general population as well as the availability of disease-modifying therapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears in the late-stage activation of T cells and can serve as a marker of activated T cells ( 53 ). HLA-DR + T cells are thought of highly proliferative and short-lived ( 54 ) and HLA-DR + Tregs subset is described to be more cytotoxic ( 55 ). Report revealed that HLA-DR + T cells are elevated in SFTSV-infected patients ( 53 ).…”
Section: Discussionmentioning
confidence: 99%